Three-Dimensional Modeling of the Heat-Affected Zone in Laser Machining Applications. (9th November 2008) - Beresna, Martynas; Gertus, Titas; Tomašiūnas, Rolandas; Misawa, Hiroaki; Juodkazis, Saulius
Abstract : Thermal load as well as its three-dimensional (3D) spatial distribution has been estimated inside representative materials: glass (low thermal diffusion), silicon (semimetal properties), and sapphire (a crystalline dielectric of a high thermal conductivity) for typical laser processing and direct laser writing applications. The 3D temperature distribution allows to calculate thermal stress around the focal region. This provides an assessment tool for optimization of laser microprocessing conditions for controlled laser dicing and cutting applications.